Life satisfaction and economic outcomes in Germany pre- and post-unification - Richard A. Easterlin; Anke C. Zimmermann (Institute for the Study of Labor (IZA), 2006)
Throughout Germany real income has trended upward since 1991, but life satisfaction has risen in the East, fallen in the West, and been fairly stable for Germany as a whole. By 1997 the initial excess of West over East Germany was cut by over one-half; since then, the differential has changed very little, and even edged slightly upward. The post-unification decline in West Germany appears to be a break with the pattern in the seven years prior to unification and occurs among Germans, European foreigners, and Turkish foreigners. After 1997, Turkish foreigners, unlike the others, continue to decline in life satisfaction, and by 2004, their initial excess over East Germans largely disappears. The life satisfaction of post-unification migrants from East Germany to the West is somewhat less than that of Germans and European foreigners in the West, but higher than that of Turkish foreigners and of Germans in East Germany. Migrants from the West to East Germany have life satisfaction about equal to that of Germans in that region. Trends and differences in overall life satisfaction are most systematically related to reports on satisfaction with income, next to the unemployment rate, and least of all, to absolute real income.
urn:nbn:de:101:1-20080509203
Keywords: 330